The Psychometric Properties of the Norwegian Teacher Version of Behavior Rating Inventory of Executive Function (BRIEF) - Køhn, Kristian; Halvorsen, Marianne (PsykTestBarn, 2020)
Description: The Behavior Rating Inventory of Executive Function Teacher Form (BRIEF; Gioia et al., 2000) is a standardized questionnaire for pupils aged 5-18 years. The International licensee is Psychological Assessment Resources Inc. The Norwegian Adaptation was published and originally translated to Norwegian in 2004 (Sørensen & Hysing, 2014). The questionnaire assesses executive functions in everyday life. The questionnaire consists of 86 items and is comprised of eight scales as well as several index scales including the Behavioral Regulation Index (BRI), the Metacognition Index (MI) and the Global Executive Composite (GEC). Interpretation of BRIEF scores and profiles requires diagnostic expertise (clinical psychologist/medical doctor) as well as relevant training in the interpretation of psychological tests from an accredited college or university. Literature search: A total of 175 Scandinavian articles were identified, including three Norwegian studies which contained relevant psychometric data such as mean values and evidence of reliability and validity. The samples were Norwegian children in elementary school, with subsamples of children in treatment at an outpatient psychiatric clinic or receiving school psychology services. Psychometrics: There is some evidence supporting the use of the original American scale norms in Norway; mean values for fourth-grade Norwegian pupils were mainly consistent with the original American norms. In addition, Norwegian studies further support the reliability, construct validity, and the sensitivity of the instrument. Conclusion: The BRIEF teacher form should be used with caution in Norway. There is a possibility of underestimating the child`s difficulties on the Flexibility and Planning/Organizing scales when using the original American norms.